PF-16 Traditional Chinese Veterinary Medicine Approach for Canine Inflammation Bowel Disease Therapy - Zulfa Ichsanniyati; Siti Zaenab; Bagus Satrio (Hemera Zoa, 2018)
IBD is thought to originate as a consequence of a deregulation of mucosal immunity in predisposed animals3. The loss of tolerance to antigens (food, intestinal bacteria, etc.) is one of the most studied mechanisms that could justify the development of chronic intestinal inflammation1,4,6. The main difficulties in treating dogs with IBD originate from an incomplete understanding of the pathophysiological basis of these diseases. Mostly therapi will fall between steroid and other immunosupresive drug, metronidazole antibiotic and novel food. However this case usually recurrence without unidentifying aethiology.Chronic indigestion or secondary to the inflammation in chronnic recurence IBD mostly cause by the Damp that accumulate in the spleen and intestine2. Damp interferes Spleen to transforming and transporting food which leads to lose stool. Damp that to long accumulate in the Spleen will damage Spleen Yang and Qi. The Spleen will lose one of it main function to controlling the Blood which is keeps the blood circulating within vessels, prevent extravassasion leading to bloody diarrhea and anemia7.